Factors Affecting the Students’ Coping Strategy Dealing with National Nurse Competence Examination: Which are More Related? - Harjanto, Totok; Pratiwi, Widowati Budi; Puspasuci, Sunika; Hapsari, Lesiana Eka (Jurusan Keperawatan FIKES UNSOED, 2018)
National nurse competency examination (UKNI) aims to measure standards of nurses approved with Nurse’s Register License. This examination could induce anxieties that affect students’ readiness, performance and graduation. The objective of this study was to describe coping strategy in dealing with national nurse competency examination and its related factors which are anxiety and perception. A descriptive study was performed on 80 nursing students at clinical rotation nursing program who enrolled in March 2017’s nurse competency examination. German Test Anxiety Inventory (TAI-G), Perception Questionnaire and Coping Strategy Indicators (CSI) were used to measure exam anxiety, student’s perception and coping strategy respectively. The results show that regarding to students’ perception, 37 students (46,3%) demonstrated good perception and the rest (58,7%) showed poor perception. Forty two students (52.5%) experienced low anxiety and the rest (47.5%) experienced high anxiety. In regards to coping strategy in dealing with competence examination, 44 students were in good category (55%), while 36 students (45%) were in poor category. This study implies that information about the national nurse competence examination should be provided as earlier as possible, so that students could make adequate preparation.